2012
DOI: 10.7732/kjpr.2012.25.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Assessment on Antioxidant Potential and Enzyme Activity of Some Economic Resource Plants

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Other studies showed that the scavenger activity of the radical DPPH of the roots of Phragmites communis is very low with high concentrations that comes up 2500 mg/l and gave only a percentage of 7.8±0.32% [Boo et al 2012].…”
Section: Dpph Assaymentioning
confidence: 98%
“…Other studies showed that the scavenger activity of the radical DPPH of the roots of Phragmites communis is very low with high concentrations that comes up 2500 mg/l and gave only a percentage of 7.8±0.32% [Boo et al 2012].…”
Section: Dpph Assaymentioning
confidence: 98%
“…The investigation of the antioxidant activity of natural substances is based on the measuring of the electron donor capacity of DPPH with the ability to inhibit the oxidation by donating electrons in free radicals causing this lipid peroxidation (Boo et al, 2012), that is, free radical are known to be a major factor in biological damages, and DPPH has been used to evaluate the free radical-scavenging activity of natural antioxidants (Yokozawa et al, 1998;Zhu et al, 2001). Active oxygen caused by in vivo metabolism removed by the body's antioxidant system, but excessive free radicals induced stress, causing the lipid peroxidation by combining with unsaturated fatty acids in the cell membrane, and brought intracellular structural and functional damage.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Most of the antioxidant compounds in a typical diet are derived from plant sources and belong to various classes of compounds with a wide variety of physical and chemical properties. The main characteristic of an (Prakash et al, 2001;Boo et al, 2012). In response to the increased production of oxygen radicals the capacity of the antioxidant defense system is increased, but in most situations the response is moderate (Foyer et al, 1994).…”
mentioning
confidence: 99%